(untitled) (Citizenship in Action: Extension and Culture Magazine, 2023)
This article brings a brief summary about the Núcleo Extensionista Rondon – NER/UDESC, its action inside of the Santa Catarina state, Brazil and abroad, also its structure and experiences, since its foundation, extensionist practices with community where the activities of Núcleo Extensionista Rondon have been happened. The text analyzes the indivisibility between Teach, Research and Extension like practical benchmark of the actions from NER/UDESC, and putting together the academic, personal and professional development of the extensionists who part of it have been. Through practical examples, experienced in different scenarios of society, starting from NER/UDESC, contextualizes the importance of extensionists activities developed, considering the aspect that involves the academic formation aligned to the areas of university extension.